Services for trade competitiveness : country and regional assessments of services trade - Hollweg, Claire H. (ed.); Saez, Sebastian (ed.) (Wishington World Bank Group, 2019)
Recognizing that services affect the ability of countries and their firms to compete on international markets, the Trade and Regional Integration Unit of the World Bank has developed an extensive work program to promote the performance of countries domestic services sector, including in services trade. This volume presents selected applications of the new methodologies developed by the Unit to assess the competitiveness of countries services sector, identify the types of barriers to services that exist in the regulatory environment, and the resulting policy implications. Its assessments are designed for a wide audience, including policy makers in developing countries and development practitioners in international organizations, policy-making institutions, and academia. The purpose of this volume to help developing countries make informed policy choices to increase their chances of benefiting from the increasing prominence of services in international trade.
Keywords: Service industries; Developing countries; Government policy